2018
DOI: 10.1002/jcb.27407
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanisms of regulation of the expression and transcriptional activity of hepatocyte nuclear factor 4α

Abstract: Hepatocyte nuclear factor 4α (HNF4α) is a master regulator of development and function of digestive tissues. The HNF4A gene uses two separate promoters P1 and P2, with P1 products predominant in adult liver, whereas P2 products prevalent in fetal liver, pancreas, and liver/colon cancer. To date, the mechanisms for the regulation of HNF4A and the dynamic switch of P1-HNF4α and P2-HNF4α during ontogenesis and carcinogenesis are still obscure. Our study validated the previously reported self-stimulation of P1-HNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 55 publications
3
18
0
Order By: Relevance
“…In this study, HNF4A-AS1 was identified as a lncRNA upregulated in NB tissues and cell lines. Previous studies indicate that HNF4A-AS1 participates in mucosal injury in Crohn's disease [51], and serves as a HNF4A target gene in hepatocellular carcinoma cells [52]. Our evidence indicated that HNF4A-AS1 facilitated the expression of HNF4A at transcriptional level, and tumor promoting functions of HNF4A-AS1 were mediated, at least in part, through interacting with hnRNPU protein.…”
Section: Discussionsupporting
confidence: 51%
“…In this study, HNF4A-AS1 was identified as a lncRNA upregulated in NB tissues and cell lines. Previous studies indicate that HNF4A-AS1 participates in mucosal injury in Crohn's disease [51], and serves as a HNF4A target gene in hepatocellular carcinoma cells [52]. Our evidence indicated that HNF4A-AS1 facilitated the expression of HNF4A at transcriptional level, and tumor promoting functions of HNF4A-AS1 were mediated, at least in part, through interacting with hnRNPU protein.…”
Section: Discussionsupporting
confidence: 51%
“…Guo and Lu reported that the expression of HNF4α-AS1 was strongly activated by P1-HNF4α, which is predominantly produced in adult liver, but not P2-HNF4α, which is prevalent in fetal liver, pancreas, and liver/colon cancer. Therefore, HNF4α-AS1 might be a biomarker for P1-HNF4α expression and might be involved in the functional regulation of the liver-specific P1-HNF4α [63]. The knockdown of HNF4α also showed to repress the expression of HNF4α-AS1 in HepaRG cells, which further validated the idea the HNF4α-AS1 was regulated by HNF4α [60].…”
Section: Relations Of the Regulation Of Expression Between Hnf1α And Hnf1α-as1 And Between Hnf4α And Hnf4α-as1supporting
confidence: 61%
“…In human colon tumors, P1-driven HNF4A is either lost or localized in the cytoplasm due to an isoform-specific phosphorylation of HNF4A by SRC tyrosine kinase affecting protein stability, nuclear localization, and transactivation function of P1-driven, but not P2-driven, isoforms [ 133 ]. In contrast, P2-driven HNF4A is induced in colon cancer though combined actions of Paired Box 6 (PAX6) and HNF1A [ 177 ]. In line with the P1:P2 ratio playing a key role in the pathophysiology of colon cancer, tumor load and size were increased in mice which could only produce P2-driven HNF4A isoforms in a model of colitis-associated colon cancer, while restricted expression of P1-driven isoforms and led to fewer and smaller tumors [ 32 ].…”
Section: Hnf4 Loss Contributes To Loss Of Identity In Diseasementioning
confidence: 99%